SIMULATION OF PULVERIZED COAL FIRED BOILER: REACTION CHAMBER - Rodrigues, C. P.; Lansarin, M. A.; Secchi, A. R.; Mendes, T. F. (Revista de Engenharia Térmica, 2005)
This work is part of a joint project to built a computational tool for power plant simulation, dealing specifically with the reaction chamber (place of the boiler where the fuel is burned). In order to describe the conversion of chemical energy to thermal energy, an onedimensional pseudo-homogeneous mathematical model, with variable physical properties, and based on mass and energy balances, was developed. The equations were implemented in the gPROMS simulator and the model parameters were estimated using the module gEST of this software, with experimental data from a large-scale coal-fired utility boiler and kinetic data from the open literature. The results showed that the model predicts the composition of the outlet combustion gas satisfactorily.